Learning Fiqh Based on the TAPPS (Think Aloud Pair Problem Solving) Method in Improving Student Learning Outcomes - Fahmi Siti Fatimah; Hasyim Asy'ari; Anis Sandria; Juli Amaliya Nasucha (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The research aimed to determine how fiqh learning is based on the TAPPS (Think Aloud Pair Problem Solving) method in improving student-learning outcomes at MAN 1 Mojokerto. This research used qualitative research. The researcher used a case study approach. The Data was collected through observation, interviews, and documentation. This research showed that the process and implementation of fiqh learning include 3 processes, namely planning, implementation, and evaluation where planning included all initial activities in implementing the TAPPS Method. The implementation included the process of implementing RPP (Learning Implementation Plan) in applying the TAPPS Method, evaluation included a final assessment of the learning process so that it could find out student learning outcomes Furthermore, learning outcomes included three aspects of assessment, namely, assessment of affective (attitude), cognitive (ability) and psychomotor (skills) aspects. Students had a significant increase in learning outcomes and had good interpersonal skills development. Appraising from the progress of the student learning process, the development of interpersonal skills possessed by students was oriented to thinking skills which included intellectual abilities. In addition, students also could master and develop well what they have learned.